PENGARUH SUSTAINABILITY REPORTING TERHADAP KINERJA KEUANGAN PERUSAHAAN PUBLIK DARI SISI PROFITABILITY RATIO - Ria Natalia (Business Accounting Review, 2014)
Sustainability report contains the financial performance and non –financial performance . In recent years, has been realized the importance of this disclosure through its impact on financial performance. This study aimed to examine the relationship between indicators of sustainability reporting and the company’s profitability ratio. This study used secondary data. The independent variable in this study was the disclosure of Sustainability report that divided into the performances of disclosure of economic, environmental and social that measured by using SRDI index . The independent variables were measured by using the disclosure index . GRI ( Global Reporting Initiative ) would be used as a guide of sustainability report as a basis for measuring the index . The dependent variable used was the profitability ratio including profit margin , ROA and ROE as a measure of financial performance. The sample was 10 companies that published the sustainability report in three consecutive years of 2009-2011 and could be accessed through the companies’ websites and the website of National Center for Sustainability Reporting and these companies had already published the Annual Financial Statements in 2010-2012 which could be accessed through the companies’ websites. The results showed that there was presence significant negative affect on economic performance disclosure and no positive relationship significant for environmental performance , as well as a significant positive affect on social performance to financial performance of the Profitability Ratio.